Identifikasi Solusi Problematika Pelafalan dan Penulisan Huruf Hijaiyah Pada Santri Usia Dini di TPQ Al-Firdaus Sidoarjo - Husni Abdillah; Rokhmatus Solicha; Syahidah Sahda Shofariyah; Indah Machmudah; Putri Dzaqiyatus Sholihah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
The purpose of this study was to describe the problems experienced by Al-Quran educational institute students in pronouncing and writing Hijaiyah letters. To achieve the research objectives, descriptive qualitative research was used. The data collection methods used in this study were observation, documentation, and interviews. Researchers used observation to collect data, namely with an observation instrument on students aged 3-5 years at Al-Firdaus Al-Qur’an Educational Institute of Sidoarjo who have various characters in the pronunciation and writing of Hijaiyah letters. While the interviews were used to deepen the analysis of the problems of pronouncing and writing Hijaiyah letters. The results of the research are as follows: problematic ability to say Hijaiyah letters arises because students have delays in aspects of language development, lack of focus on paying attention to the teacher. As for the problems in the ability to pronounce and write Hijaiyah letters occur in students and to overcome obstacles, several methods are applied. The child's ability is observed first before determining the appropriate method and is felt to be effective. Some of the methods used are the Musyfahah or Tongue Fighting Method, the 'Ardul Qira'ah or Reading Deposit Method, and finally the Tracing Method